2009
DOI: 10.1002/eji.200838472
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of scavenger receptor cysteine‐rich WC1 is required for the WC1‐mediated potentiation of TCR‐induced T‐cell proliferation

Abstract: Workshop cluster 1 (WC1) molecules are transmembrane glycoproteins uniquely expressed by cd T cells. They belong to the scavenger receptor cysteine-rich superfamily and are encoded by a multi-gene family, which is divided on the basis of antibody reactivity, into three groups, WC1.1, WC1.2, and WC1.3. The potential role of WC1 as a co-stimulatory molecule for the cd TCR is suggested by the presence of several tyrosinebased motifs in their intracellular domains. In this study, we found that WC1 was constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 45 publications
7
55
0
Order By: Relevance
“…We have previously shown that the gd T cell specific WC1 transmembrane proteins, members of the ancient and conserved scavenger receptor cysteine rich (SRCR) receptor superfamily closely related to CD163 molecules (17), can act as coreceptors for gd T cells. Ab-mediated crosslinking of WC1 with the TCR-CD3 complex potentiates T cell activation, whereas ligation of WC1 alone has no effect or is inhibitory (18,19). This potentiation of TCR signaling requires the phosphorylation of a tyrosine in the cytoplasmic tails of WC1 (19,20) and is modulated by an endocytic dileucine motif and membrane proximal serines (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the gd T cell specific WC1 transmembrane proteins, members of the ancient and conserved scavenger receptor cysteine rich (SRCR) receptor superfamily closely related to CD163 molecules (17), can act as coreceptors for gd T cells. Ab-mediated crosslinking of WC1 with the TCR-CD3 complex potentiates T cell activation, whereas ligation of WC1 alone has no effect or is inhibitory (18,19). This potentiation of TCR signaling requires the phosphorylation of a tyrosine in the cytoplasmic tails of WC1 (19,20) and is modulated by an endocytic dileucine motif and membrane proximal serines (21).…”
mentioning
confidence: 99%
“…Ab-mediated crosslinking of WC1 with the TCR-CD3 complex potentiates T cell activation, whereas ligation of WC1 alone has no effect or is inhibitory (18,19). This potentiation of TCR signaling requires the phosphorylation of a tyrosine in the cytoplasmic tails of WC1 (19,20) and is modulated by an endocytic dileucine motif and membrane proximal serines (21). Following activation, WC1 colocalizes with the gd TCR-CD3 complex in lipid rafts (22).…”
mentioning
confidence: 99%
“…Coligation of WC1 with TCR/CD3 transduces a positive signal (21,22), which is dependent upon the phosphorylation of a tyrosine in the WC1 cytoplasmic domain (22,23). Each WC1 molecule has 6-11 extracellular group B scavenger receptor cysteine-rich domains of ∼100 aa, each containing three or four disulfide bonds and a hydrophobic core.…”
mentioning
confidence: 99%
“…The cytoplasmic domains of WC1 proteins are similar to those of CD3g, CD3d, and CD4, containing two consensus [DE]XXXL[LIM] dileucine motifs, multiple serines, and two to four YXXØ tyrosine-based motifs (20,23). We showed previously that mutation of the tyrosine of one of the YXXØ tyrosine-based motifs in WC1-3 does not affect phorbol ester-induced endocytosis, suggesting that the dileucine motifs may instead regulate WC1 phorbol esterinduced endocytosis (22). In this study, we investigate the requirement for two serines and the membrane proximal dileucine motif in phorbol ester-induced WC1 endocytosis in both HEK-293T cells and Jurkat T cells.…”
mentioning
confidence: 99%
“…Study with wide range of monoclonal antibodies revealed that WC+1 + corecptor is made of tow nonoverlaping variants, WC+1.1 and WC+1.2, whereas WC+1.3 variant is coexpressed with the WC+1.1 [20]. WC+1 + coreceptors play major role in mediating the costimulatory signal in activation of T cells [21]. Further studies on the role of the WC+1 + have revealed a diverse genetic variation which could reach to at least 13 WC+1 + genes on the bovine chromosome 5 [22].…”
Section: Workhop Cluster+1mentioning
confidence: 99%